Switzerland : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper describes economic developments in Switzerland during the 1990s. Between 1990 and 1993, real GDP fell by a cumulative 1u percent. The tightening of monetary policy in response to rising inflation in the late 1980s induced a contraction in domestic demand that sent the economy into decline in 1991. This decline was prolonged by the downturn of other European economies during 1992-93, although the latter had only a modest effect on Swiss exports, which continued to grow slowly.